Major Soils of Rayalseema Region: A Case Study at Rayachoty Mandal, YSR Kadapa District, Andhra Pradesh - M., Chandrakala (Chronicle of Bioresource Management, 2025)
Based on a detailed soil survey at a 1:10000 scale, Alfisols, Inceptisols, and Entisols were the major soils in the Rayachoty Mandal, YSR Kadapa district, Andhra Pradesh, belonging to the Rayalseema region. Calcium carbonate equivalent ranged from 0 to 13.39 %. Clay content ranged from 4.62 to 23.32 % on the surface and from 8.10 to 40.55% on the subsoils. The CEC ranged from 2.80 to 15.60 cmol (+) kg–1 in the surface and 4.10 to 18.30 cmol (+) kg–1 in the subsoil. Base saturation ranged from 56.76 to >100%. Soils are strongly acidic to strongly alkaline. Organic carbon is low to high. Available P, K and S are low. DTPA extractable Fe, Mn and Cu are sufficient, and Zn is deficient, and boron is low. Soils were classified as Lithic Rhodustalfs, Lithic Ustipsamments, Rhodic Paleustalfs, Typic Haplustalfs, Typic Haplustepts, Typic Rhodustalfs and Typic Ustorthents. Soils were mapped into 10 soil series and 53 mapping units.